2019
DOI: 10.1002/cpp.2365
|View full text |Cite
|
Sign up to set email alerts
|

Emotional development in eating disorders: A qualitative metasynthesis

Abstract: Emotions are considered to be an important feature in eating disorders. The present study aimed to conduct a systematic review and metasynthesis of qualitative studies, which considered the role of emotions in eating disorders in order to gain further insight on how these individuals experience various emotions and the strategies they use to manage them. Databases including Web of Science, PsychInfo, EMBASE, Medline, and the Cochrane library were searched for qualitative studies. The search identified 16 relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 93 publications
4
16
0
Order By: Relevance
“…Tantillo and colleagues [ 22 ] write about the disconnection pointed to by adults with an ED and their family members in MFT. This is a reference to the loss of connection between the patients and their feelings and the disconnection between family members one from another (which may be caused by feelings of guilt or blame about the cause of the ED, and poor emotional bonds [ 51 ], or by patients withholding information in order to maintain their autonomy [ 20 ]), to the effects of not knowing what best to say, of trying to avoid conflict, of misunderstandings and of sheer exhaustion. Also, disconnection from friends, colleagues, the wider family and the outside world generally [[ 22 ], p. 279).…”
Section: Discussionmentioning
confidence: 99%
“…Tantillo and colleagues [ 22 ] write about the disconnection pointed to by adults with an ED and their family members in MFT. This is a reference to the loss of connection between the patients and their feelings and the disconnection between family members one from another (which may be caused by feelings of guilt or blame about the cause of the ED, and poor emotional bonds [ 51 ], or by patients withholding information in order to maintain their autonomy [ 20 ]), to the effects of not knowing what best to say, of trying to avoid conflict, of misunderstandings and of sheer exhaustion. Also, disconnection from friends, colleagues, the wider family and the outside world generally [[ 22 ], p. 279).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been suggested that self-starvation itself works as an emotion regulation strategy which reduces both the internal experience and external expression of emotions through ( 153 ). By suppressing physiological responses and arousal, starvation can help the person escape and avoid unwanted emotions ( 153 , 154 ). If no alternative methods are available, the person may over time become reliant on starvation as their sole emotion regulation strategy due to its numbing effect ( 155 , 156 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been suggested that self-starvation itself works as an emotion regulation strategy which reduces both the internal experience and external expression of emotions through (Haynos & Fruzzetti, 2011). By suppressing physiological responses and arousal, starvation can help the person escape and avoid unwanted emotions (Haynos & Fruzzetti, 2011;Henderson, Fox, Trayner, & Wittkowski, 2019). If no alternative methods are available, the person may over time become reliant on starvation as their sole emotion regulation strategy due to its numbing effect (Oldershaw, Startup, & Lavender, 2019;Schmidt & Treasure, 2006).…”
Section: Discussionmentioning
confidence: 99%